Irritable bowel syndrome: systematic review of origin, pathology, diagnosis and treatment - Kacper Kwiliński; Roksana Zdunek; Karolina Strus; Magdalena Madera; Adrian Kruszewski; Anna Dąbrowska; Natalia Paduszyńska; Barbara Wawrzyńska (Nicolaus Copernicus University in Toruń, 2024)
Irritable bowel syndrome is the most common problem of gastrointestinal practice worldwide. It contains group of symptoms that affect the gastrointestinal tract. People with IBS may experience abdominal pain, diarrhea, constipation, cramps.   It's still being under discussion whether the irritable bowel is a pathological or a psychological syndrome.  People report various symptoms, so they also consult doctors of different medical specializations.  For the same reason doctors may have problems with accurate diagnosis of IBS. As evidenced by recent studies, IBS is associated with psychological distress and impaired quality of life. It's also important from economical and medical care system point of view - they utilize the health care system to a greater degree than patients without this diagnosis. The aim of this review is to provide a comprehensive evidence-based review of the diagnosis, pathogenesis and treatment to guide clinicians diagnosing and treating their patients.